PEMANFAATAN PERMAINAN TRADISIONAL UNTUK MENSTIMULASI PERKEMBANGAN ANAK USIA 5-6 TAHUN DI PAUD PERMATA AMPERA PONTIANAK. - Tia, Maria Eka Sulis; R, Marmawi; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2023)
This study aims to: (1) describe the use of traditional games to stimulate the development of children aged 5-6 years at PAUD Permata Ampera Pontianak. (2) describes the use of traditional kite games, coconut baroque stilts, and jumping rope to stimulate the development of children aged 5-6 years at PAUD Permata Ampera Pontianak. This research is a qualitative research with a qualitative descriptive approach. The instruments in this study were observation sheets to find out the use of traditional kite games, coconut shell stilts and jump rope to stimulate the development of children aged 5-6 years, interview guides to dig up additional information about the use of traditional games to stimulate children's development and documentation. The results of research through observation and interviews show that the use of traditional kite games, coconut shell stilts, and rope jumping in learning can stimulate children's development. The stimulation of children's development through these three traditional games is in the process of the game being carried out, starting from the initial preparation until the game is finished being played. Children discuss giving opinions, playing games, encouraging friends and helping friends while playing, invited to pray before and after playing , and the child is explained that the materials used for the game to be played are obtained from materials provided by nature.